The Value of Caring for Early Childhood in the Storybook “The Story of the Shade Tree” by Liza Erfiana - Elda Zein Bilqis, Iqlima (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study aims to determine the value of caring for the environment, especially for trees and plants contained in the storybook